Taxonomic novelties in Andean Senecioneae (Compositae) - Calvo, Joel; Arnelas, Itziar; Minga, Danilo (Phytotaxa, 2019)
Two new Andean species belonging to the tribe Senecioneae (Compositae) are described herein, i.e., Dendrophorbium azoguesense from Ecuador and D. varicosum from Bolivia. The species Pentacalia todziae is recorded for the first time in Ecuador and the names Dendrophorbium onae and D. onae var. leonis synonymized to D. scytophyllum. Taxonomic discussions and diagnostic characters to differentiate each species are provided, as well as a distribution map and pictures of living plants when available.